2020
DOI: 10.18632/aging.103672
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in vascular size and density in transgenic mice with Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is one of the most common neurodegenerative diseases. Here, we used vessel size imaging to investigate the specific microvascular changes and most susceptible brain regions during AD progression in an amyloid precursor protein 23 (APP23) transgenic AD mouse model. Using 9.4 Tesla magnetic resonance imaging (MRI), the values of microvascular density (Density), mean vessel diameter (mVD), and vessel size index (VSI) were compared between APP23 and wild-type (WT) mice at 3, 6, 9, 14, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…A recent MRI-based study showed that the microvessel density in AD-model mice decreased, but mVD and VSI in AD-model mice increased in the regions of the hippocampus and brain cortex. 38 These were consistent with our results, which showed decreased Q and increased mVD and VSI in the cortex and hippocampus of AD-model mice. In addition, our results also showed changes in the dentate gyri and CA1 areas.…”
Section: Microstructures Are Damaged In the Ad-model Tg Mousesupporting
confidence: 93%
See 3 more Smart Citations
“…A recent MRI-based study showed that the microvessel density in AD-model mice decreased, but mVD and VSI in AD-model mice increased in the regions of the hippocampus and brain cortex. 38 These were consistent with our results, which showed decreased Q and increased mVD and VSI in the cortex and hippocampus of AD-model mice. In addition, our results also showed changes in the dentate gyri and CA1 areas.…”
Section: Microstructures Are Damaged In the Ad-model Tg Mousesupporting
confidence: 93%
“…Another biochemistry study showed microvessel injury in the AD human brain caused by an accumulation of Aβ proteins. 37 This injury can be altered in mVD and VSI in our study and the previous one by Xu et al 38 We used MvWI (ΔR2* × ΔR2) as a voxel tool to map small blood vessels. This improves the sensitivity for visualizing intracortical penetrating arterioles and venules deep within the animal brain through segmentation and quantification.…”
Section: Microstructures Are Damaged In the Ad-model Tg Mousementioning
confidence: 51%
See 2 more Smart Citations
“…Previous studies on postmortem human brains and AD mice models reported reductions in vascular density in cortex, hippocampus, and basal forebrain [6,10,44,45], but there is also considerable evidence of increased angiogenesis in both human and AD mice model brains [46][47][48][49]. Further, a recent study by Xu et al demonstrates a decrease in vascular density in aged APP23 mice, with a transient increase in density at 9 months [50]. It is worth noting that some studies and particularly older ones fail to take possible cortical atrophy into account (reviewed in [13]).…”
Section: Discussionmentioning
confidence: 97%